The Utilization of Purple Yam Mucilage for Yam Starch-Based (Dioscorea alata L.) Edible Film - Kharisma, Yulia; Ulyarti, Ulyarti; Yusfi, Liza Aulia; Lainatussifa, Lainatussifa; Framita, Rabecha Maros; Hasanah, Siti Robiatun; Damris, M (Jurnal Bio-Geo Material Dan Energi, 2026)
Edible films are thin layers used to coat food products and can be consumed along with the product itself. Previous studies have utilized purple yam starch as a base material for edible films; however, these films exhibit limitations in terms of mechanical and barrier properties. This study aims to utilize purple yam mucilage to improve the mechanical and barrier properties of purple yam starch-based edible films.  The experimental design employed a randomized complete block design (RCBD) with five ratios of water to purple yam mucilage (1:0.5, 1:1, 1:1.5, 1:2, and 1:2.5). The results showed that increasing the proportion of purple yam mucilage improved the mechanical and barrier properties of the edible films, while reducing their solubility in water to as low as 33.23%.  The best film characteristics were achieved at a ratio of 1:2.5, with a thickness of 0.14 mm, a compressive strength of 3.73 × 10⁻⁴ MPa, a water vapor transmission rate (WVTR) of 21.94 g/m²·day, a transparency value of 8.33 %T/mm, and a solubility of 33.23%.